Advertisement Remove all ads

Evaluate : (64)^(2/3) - Root(3)(125) - 1/2^(-5) + (27)^(-2/3) Xx (25/9)^(-1/2) - Mathematics

Sum

Evaluate : `(64)^(2/3) - root(3)(125) - 1/2^(-5) + (27)^(-2/3) xx (25/9)^(-1/2)`

Advertisement Remove all ads

Solution

`(64)^(2/3) - root(3)(125) - 1/2^(-5) + (27)^(-2/3) xx (25/9)^(-1/2)`

= `(4^3)^(2/3) - root(3)(5^3) - 2^5 + (3^3)^(-2/3) xx ((5^2)/(3^2))^(-1/2)`

= `4^2 - 5 - 2^5 + 3^-2 xx (5/3)^( 2 xx (-1/2)`

= `16 - 5 - 32 + 1/3^2 xx (5/3)^-1`

= `- 21 + 1/9 xx 3/5`

= `- 21 + 1/15`

= `[ - 315 + 1 ]/15`

= `- 314/15`

= `- 20 14/15`

Concept: Simplification of Expressions
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (C) | Q 1.2 | Page 101
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×